The Code of Ethics of a Laboratory Diagnostician - Szałata, Kazimierz (Studia Ecologiae et Bioethicae, 2008)
The need to establish the Code of Ethics of a Laboratory Diagnostician stems from the development of medicine in which the specialized laboratory diagnostics has been playing an increasingly important role. Not only does it help determine accurate diagnostics which enables effective therapy, but also contributes to the development of wider health service and preventive medicine. It is thus understandable that with the service providers and patients becoming increasingly aware of the importance of laboratory diagnostics, it has gained the status of the profession of public trust. In practice, it means that laboratory diagnosticians set themselves high moral and professional standards, The Code of Ethics of a Laboratory Diagnostician, the signatories of which are individual laboratory diagnosticians through their representatives who attended the Extraordinary National Meeting of Laboratory Diagnosticians on January 13, 2006, will be very important in education of specialists, the Code expresses the moral awareness of the laboratory diagnostics community, and also provides the basis for assessment of professional involvement and moral stance of the members of the Corporation. The Code of Ethics of a Laboratory Diagnostician is grounded in generally accepted ethical standards as well as the principles originating from the professional tradition, the principal standard of conduct of a laboratory diagnostician involves consideration of the welfare of a human being, which should be protected both in the individual and social context, this principle provides for the obligation to respect human dignity and establishes reference for professional practice so that its primary objective would cover service to a patient in accordance with commonly respected values such as honesty, reliability and competency.